2021
DOI: 10.1108/sbm-09-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder status in the identification, prioritization and management of college athletic donors

Abstract: PurposeThe purpose of this study is to examine how athletic fundraising managers perceive status and seek to use status to identify, prioritize and manage stakeholders within college athletics.Design/methodology/approachTo test this purpose, the researchers use the Gioia methodology to interview 19 college athletic department fundraising officers within National Collegiate Athletics Association (NCAA) institutions. Following interviews, the data were analyzed by the researchers and structured within a first-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Freeman argued that organizations must create as much value as possible for these stakeholders because they can influence strategic direction and also be influenced by the organization. There is a history of scholars applying stakeholder theory within the sport management field as well as athletic fundraising (Covell, 2004(Covell, , 2005Huml & Cintron, 2021;Steadland, 2015;Welty Peachey & Bruening, 2011). Athletic departments are multi-level organizations comprised of numerous stakeholders (athletic directors, chancellors, coaches, and donors) with influence, both internally and externally.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Freeman argued that organizations must create as much value as possible for these stakeholders because they can influence strategic direction and also be influenced by the organization. There is a history of scholars applying stakeholder theory within the sport management field as well as athletic fundraising (Covell, 2004(Covell, , 2005Huml & Cintron, 2021;Steadland, 2015;Welty Peachey & Bruening, 2011). Athletic departments are multi-level organizations comprised of numerous stakeholders (athletic directors, chancellors, coaches, and donors) with influence, both internally and externally.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, participants in the study did not expect their donations to lead to more on-field victories. Huml and Cintron (2021) examined perceived status by fundraisers as they identify, manage, and prioritize their stakeholders, finding that status was a useful tool for donor management. Walker (2015) examined athletic department donations the year following an institution's participation in the NCAA Division I Men's Basketball Final Four and major college football bowl games over a 10-year period (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Further, Stinson and Howard (2010b) found that nearly three-quarters of the donors that give charitable donations up to $5,000 do so because that is the minimum amount that they can give to still be able to receive the primary seat locations they desire. For purchasing tickets to college athletic events, multiple studies have presented a relationship exiting between a donor's charitable gift and their preferred season ticket seating options (Coughlin & Erekson, 1984;Mahony, Gladden, & Funk, 2003;Humphreys & Mondello, 2007;Huml, Brown, & Bergman, 2020;Huml & Cintron, 2021). This situation has been shown to operate as case of supply and demand, meaning that for successful athletic programs, the desire individuals have for the best seats is greater than the available seat options that facilities have, thus resulting in donors being required to make large donations to secure these prime locations (Coughlin & Erekson, 1984;Mahony, Gladden, & Funk, 2003;Humphreys & Mondello, 2007).…”
Section: Standard Donormentioning
confidence: 99%
“…While prior research has acknowledged the connection between donor motivations and fan identification (Huml, Brown, & Bergman, 2020;Huml & Cintron, 2021), a dearth of empirical examination has been conducted on student-donor programs. Therefore, the value in this study rests in its key findings, which convey the details on the essential elements necessary for constructing a student-donor membership.…”
mentioning
confidence: 99%